The Dynamics of Arabic Language Curriculum at Arabic Education Department of UIN Sunan Kalijaga Yogyakarta - Rahman, Rifqi Aulia; Kumalasari, Indah (IAIN Salatiga, 2020)
This study aimed at describing the PBA curriculum development in the period of 1975-2013, viewed from ‘continuous and changing’ perspective on its components and exploring its causes. This was qualitative research with a historical approach, so that the data analysis was done by descriptive qualitative analysis. The results were as follows: first, in terms of the authority in curriculum compilation before KBK, the Government was quite dominant, and departments had role as curriculum implementers, although in the following years they were authorized to develop their own curriculum. Second, there were differences in naming the components and compositions of the curriculum structure in courses. Third, the learning process that was originally a transfer of knowledge (before KBK), teacher centered (TCL), and content based, turned into a method of inquiry (KBK) and sstudent centered learning (SCL). The outcomes shifted into the involvement of the community as stakeholders. Fourth, Arabic learning objective shifted from language goals that are only passive to holistic. The learning process also shifted on the materials, approaches, methods, techniques and evaluation.